Síntese e atividade biológica do derivado 6-formil-oxamniquina - Almeida, Adelia Emilia de [UNESP]; De Souza, Ana Luiza Ribeiro [UNESP]; Allegretti, Silmara Marques; Frezza, Tarsila Ferraz; Pinto, Mara Cristina [UNESP]; Ferreira, Antônio Gilberto; Chin, Chung Man [UNESP] (FapUNIFESP (SciELO), 2008)
Schistosomiasis, an important disease in Brazil, is caused by a trematode of the genus Schistosoma, reaching millions of person in one of the most endemic region of this disease in the whole globe. The main goal of this work was to syntetize the 6-formyl- oxamniquine derivative and evaluate its biological activity. The 6-formyl-oxamniquine derivative was obtained by the oxidation of oxamniquine with MnO 2, applying CH 2Cl 2 as solvent at room temperature for 24 hours. The obtaintion of 6-formyl-oxamniquine derivative compound was confirmed by IR spectroscopy and 13C NMR and 1H NMR, presenting similar activity when compared to the commercial oxamniquine (Mansil®).
Synthesis and biological activity of 6-formyl-oxamniquine derivative
Keywords: Ooxamniquine; Schistosoma mansoni; Schistosomiasis; 6 formyl oxamniquine derivative; manganese oxide; oxamniquine; unclassified drug; Brazil; carbon nuclear magnetic resonance; drug activity; drug structure; drug synthesis; infrared spectroscopy; proton nuclear magnetic resonance; schistosomiasis